How does a short, interrupted recovery break affect performance and how is it assessed? A study on acute effects - Pelka, M.; Ferrauti, A.; Meyer, T.; Pfeiffer, M.; Kellmann, M. (International Journal of Sports Physiology and Performance, 2017)
A recovery process with optimal prerequisites that is interrupted is termed disrupted recovery. Whether this process has an influence on performance-related factors needs to be investigated. Therefore, the aim of this study was to examine how a short disturbance of a recovery phase is assessed and whether subsequent repeated-sprint performance is affected by it. A quasi-experimental 2 × 2-factor crossover design with 34 sport-science undergraduate students (age 20.3 ± 2.1 y) was applied. Factors were the type of intervention (power nap vs systematic breathing; between-subjects) and the experimental condition (disturbed vs nondisturbed break; within-subject). Repeated-sprint performance was measured through 6 × 4-s sprint protocols (with 20-s breaks) before and after a 25-min recovery break on 2 test days. Subjective evaluation of the interventions was measured through the Short Recovery and Stress Scale and a manipulation check assessing whether participants experienced the recovery phase as efficacious and pleasant. Regarding the objective data, no significant difference between sprint performances in terms of average peak velocity (m/s) on the treadmill was found. The manipulation check revealed that disturbed conditions were rated significantly lower than regular conditions in terms of appreciation, t31 = 3.09, P = .01. Short disturbances of recovery do not seem to affect subsequent performance; nevertheless, participants assessed disturbed conditions more negatively than regular conditions. In essence, the findings indicate a negligible role of short interruptions on an objective level. Subjectively, they affected the performance-related assessment of the participants and should be treated with caution.